The development of theoretical, methodological and practical recommendations of the innovative development vectors of business process reengineering and strategic management of enterprises - Mandych, Oleksandra; Mykytas, Arkadii; Ustik, Tetiana; Zaika, Svitlana; Zaika, Olena (Technology audit and production reserves, 2021)
The object of research is the reengineering of business processes, which is used to increase the effectiveness of strategic management of an enterprise, which will create a new type of environmental enterprise «bioalliance». One of the most problematic places is the possibility of conducting marketing research to ensure the competitiveness of enterprises. The paper used the hypothetical method in substantiating the theoretical and methodological principles of organization and functioning of bio-alliances as the basis of bio-economy for rural areas. The study used the economic-statistical method, ranking of economic zoning, correlation and regression and cluster analysis. These methods were used in the elaboration of directions, sources and strategies of development, components of system and process management, state support for the implementation of traditional and new socio-economic and environmental functions. Also in the course of the work, methods of ideal modelling, mathematical modelling and programming, abstract-logical and structural-logical, extrapolation, expert evaluations, surveys, observations, qualitative and quantitative, imaginary and social experiments were used. The results of the market analyses of agricultural companies showed the inexpediency of agricultural companies. Based on the research, modelling and re-engineering of business processes through the implementation of organisational, corporate, business and functional strategies was proposed. The new form of agrarian enterprises, proposed in the work, is «bioalliance», based on the principles of integration of tourism sphere, sphere of organic production and production of eco-commodities, as well as using bio-resources as the main source. Compared to similar known methodologies of strategic management, the proposed methodology provides enterprises with a high level of importance in the regions, increasing the efficiency of the use of the resources available in their ownership. And also to allocate new market segments in order to attract not only existing, but also potential consumers.